2005
DOI: 10.1021/jp0482868
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction Structure Analysis of MCM-48 Mesoporous Silica

Abstract: The structure of MCM-48 mesoporous silicate materials has been fully characterized from X-ray diffraction data by applying recently developed methods of mesostructure analysis and full-profile refinement. The pore wall thickness of both as-made and calcined MCM-48 was determined with high precision to be 8.0(1) Angstrom. No regular variations of the wall thickness were detected, but its density was found to be ca. 10% higher in the low-curvature regions. The surfactant density in the pores was assessed around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 22 publications
5
42
0
Order By: Relevance
“…They exhibit high intensity peaks (211) followed by a smaller one (220) at 2y ¼ 2-31, whereas several other peaks are observed at 2y ¼ 4-81. Such patterns correspond to the Ia3d cubic symmetry for MCM-48 type of mesoporous silica materials [21]. As shown in Fig.…”
Section: Characterizationsupporting
confidence: 56%
“…They exhibit high intensity peaks (211) followed by a smaller one (220) at 2y ¼ 2-31, whereas several other peaks are observed at 2y ¼ 4-81. Such patterns correspond to the Ia3d cubic symmetry for MCM-48 type of mesoporous silica materials [21]. As shown in Fig.…”
Section: Characterizationsupporting
confidence: 56%
“…The cubic unit cell for the Ia 3d bi-continuous phase for the rods model and the G-surface model. Using the G-surface model, different methods can be used [14] to take into account the thickness of the film L (a) a linear profile along the normal at each point of the surface [47] (b) a convolution by an infinitely thin shell [48] (c) a lattice method with the calculation of the distance to the G-surface [49] (d ) the iso-density surfaces using the nodal surfaces approximation [50].…”
Section: Drementioning
confidence: 99%
“…Garstecki & Holyst [15,[54][55][56][57], Harper et al [47], Enlow et al [49] took into account the thickness either by a segment of length L oriented at each point along the normal to the G-surface, or using a lattice model (figure 5). Using parallel nodal surfaces (see equation (6.4) and figure 5), Solovyov et al [50] obtained a very precise modelization of a mesoporous Ia 3d phase based on more than 25 Bragg reflections. It is found that the thickness of the silica region is almost constant and homogoenous, with a slightly higher density (10%) at the flat points of the G-surface.…”
Section: Drementioning
confidence: 99%
“…Deposition of amorphous minerals by sol-gel reactions over these self-assembled 2D or 3D surfactant or amphiphile templates produces mesoporous materials with highly ordered hollow architecture after removal of the surfactants, the periodicity of which may be identified by small-angle XRD (Li and Shi 2014). A well-known example is mesoporous silica (Li et al 2012); different types of amorphous mesoporous silica exhibit several small-angle XRD peaks that are characteristic of their internal porous architecture (Kruk et al 1999(Kruk et al , 2000Solovyov et al 2005). Crystalline solids possess both long-range and short-range order; the former is characterized by well-defined, strong intensity Bragg peaks when examined by XRD.…”
mentioning
confidence: 99%